Van Gogh face to face: the portraits - Dorn, Roland (Editorial Thames y Hudson, 2001)
Includes 228 illustrations with 204 in color. An about near fine copy with some bumping to the corners and a small owner signature to the front free endpaper in a near fine dust jacket with the same bumping to the corners. An attractive monograph that focuses on the portraits by this master artist.